Measuring Bank Efficiency: Evidence from the Tanzanian Banking Sector - Ally, Zawadi; Patel, Dr. G.N. (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
The objective of this study is to measure the efficiency of commercial banks in Tanzania using a non-parametric approach, the input-oriented data envelopment analysis (DEA), both by constant return to scale (CRS) and variable return to scale (VRS). For this purpose, two outputs representing total loans and total interest income, and three inputs representing total deposits, the number of employees and total expenses are selected for seven-years (2006-2012) period in the analysis. The findings under CRS model identify four banks to be fully efficient in the year 2006, two banks in 2007 and one bank in 2008, 2009, 2010, 2011 and 2012, while VRS model results identify five banks to be fully efficient in the year 2006 and 2012, three banks in 2007 and two banks in 2008 and 2009, one bank 2010 and 2011. Four banks, Standard Charted bank, National Commercial Bank (NBC), Citibank and Barclays bank are found to be the most efficiency banks in Tanzania, which serve as the benchmark peers for inefficient banks in the sample, In addition Tobit regression has been used to determine the efficiency drivers.